A Systematic Literature Review of the Effectiveness of Mindfulness-Based Cognitive Therapy on Depression Among Older People - Patricia, Helena; Syed Elias, Sharifah Munirah; Binti Mohd Ali, Noor Azizah; Malini, Hema (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
The worldwide population of older people is rising rapidly, with projections suggesting that by 2050, persons aged 60 and over will represent 22% of the entire population. Age-related outcomes are significantly exacerbated by frailty, susceptibility, and an elevated risk of depression. Mindfulness-Based Cognitive Therapy (MBCT) has become a feasible therapeutic approach, integrating cognitive therapy with mindfulness techniques. This review systematically assesses the efficacy of MBCT in alleviating depression in the older population. This review adheres to PRISMA criteria. Seven databases (Medline, Scopus, ClinicalKey for Nursing, Ebsco, Web of Science, Cochrane Library, and Grey Literature) were examined from 2017 to 2022. Three keywords utilized were depression, elderly individuals, and MBCT. The quality of the studies was assessed using the Joanna Briggs Institute's (JBI) critical appraisal tool. Eleven studies were incorporated for the review. Research demonstrates that MBCT is advantageous in alleviating depression among the older population. This review indicates that MBCT is a potential alternative therapy for older individuals experiencing depression. It is imperative to emphasise that future research must demonstrate enhanced structural quality and require larger sample sizes.